Is the Japanese Monarchy in Crisis Due to Its Gender Bias? - Masako Kamiya (Royal Studies Journal, 2020)
Japanese monarchical succession is restricted to male offspring of imperial lineage, with the order of succession being primogeniture. This rule is not written in the 1947 Constitution—which prohibits sex discrimination in Article 14—but rather in the Imperial House Law of 1947. Given the current gender composition of the imperial family, it is not difficult to imagine a future in which the existence of the imperial system is threatened by a lack of legitimate male heirs. The article takes this reality as its starting point and evaluates the divergent attitudes of fundamentalist, orthodox, and egalitarian monarchists towards male-line primogeniture and the case for a gender-neutral monarchy in Japan. The article advocates an egalitarian view of monarchy as being most consistent with international law, Japan’s 1947 Constitution, comparative practice in contemporary monarchies, and the historical record that includes eight Japanese empresses who ruled in their own right. The article then turns to consider the contemporary role of the Emperor. Although the Japanese monarchy is comparable to others due to its exclusively symbolic and religious nature, the article notes its uniquely gendered aspects, such as the lack of public involvement and visibility of female members of the imperial family. Politicians, however, are reluctant to amend the Imperial House Law, which presents a structural barrier to gender-neutral monarchy.